Construction of Legal Relationship Between Intermediary (Plasma) and Women Workers in The Artificial Eyelash Industry - Susilo Wardani; Agustinus Supriyanto (Faculty of Law, Universitas Jenderal Soedirman, 2021)
Purbalingga Regency is famous for its artificial eyelash industry and is the second largest in the world after Goangzu, China. The company cooperates with Plasma (intermediary) to work on part of its production to replace overhead costs associated with the use of standard labor and meet fluctuating demand. The purpose of this study is to determine the construction of legal relationships between intermediaries (plasma) as employers and female workers in the false eyelash industry sector in Purbalingga Regency and to determine whether female workers in the industry have received preventive protection due to the formation of legal relationships between employers and workers through intermediaries (plasma). This research uses normative-empirical research methodology. This research focuses more on normative research supported by field data or empirical research. Based on the results of the research, the formation of legal relationships between women workers and the Plasma (company branch) is carried out through piecework agreements, but there are still restrictions that must be followed, such as the requirement that factory workers and employees have the status of casual daily laborers. Female plasma workers who work in the informal industry do not receive social protection as they should. The Social Protection System for all levels of society stipulates that the government must provide social insurance, and this is where the welfare of plasma workers becomes the responsibility of the government.Keywords: Construction of legal relations, Plasma, female workers